PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS MEDIA GAMBARUNTUK MENINGKATKAN HASIL BELAJARIPASISWAKELAS VII B SMP NEGERI 3 BANGKO TAHUN PELAJARAN 2015/2016 - Supriadi '; Darmadi '; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted to determine the learning outcome of students by implementing Discovery Learning based on image media. This research was done in class VII B SMP Negeri 3 Bangko the school year 2015/2016. This research is a classroom action research conducted in two cycles of planning, implementation, observation and reflection. The data collected in this study is the student learning outcomes that consist of cognitive (absorption and completeness of student learning), affective and psychomotor aspects and activities of teachers. Data were collected using a written test and observation sheet. The results showed that students learning outcomes consist of cognitive (absorption and completeness of student learning), affective and psychomotor aspects and activities of teachers has increased. Cognitive aspects of absorption seen in the first cycle is 79.79% (enough) increased in the second cycle into 82.67% (excellent). Mastery learning students remains 100% (category complete), both the first cycle and the second cycle. Average of affective aspects in cycle I is 73.80% (enough) increased in the second cycle into 85.22% (excellent). Average psychomotor aspects in cycle I is 82.56% (good) increased in the second cycle into 91.86% (excellent). The average activities of teachers in the first cycle is 93.19% (excellent) increased in the second cycle to 100% (excellent). It can be concluded that the application of Discovery Learning based on image media can improve learning outcomes grade science students VII B SMP Negeri 3 Bangko the school year 2015/2016.Keywords: Discovery Learning, image media, Learning outcomes